Prevalence of Metabolic Syndrome in Army Personnel Residing in Bogra Cantonment - Kabir, MA; Hossain, MR; Haque, MF; Fakir, MAH; Rahimgir, M; Momtaz, S (Journal of Armed Forces Medical College, Bangladesh, 2013)
DOI: http://dx.doi.org/10.3329/jafmc.v8i2.16354 JAFMC Vol.8(2) 2012 pp.47-51